Social Media Cartooning: Visual and Multimodal Metaphors in Iraqi Newspapers Cartoons - Hayder Tuma Jassim Alsaedi (آداب الكوفة)
The current study explores the investigation of visual and multimodal metaphors by the use of metaphorical elements in cartoons that focus on social media networking. Thirty-two cartoons, by well-known cartoonists, are gathered from the Iraqi newspapers. They are sampled and classified based on their themes. All the details of these cartoons are taken into consideration. They are verbalized into the metaphorical concepts based on Lakoff and Johnson’s (1980) Conceptual metaphor Theory. The cartoons are analyzed by using Forceville’s (1996) pictorial metaphor and Sobrino’s (2017) multimodal metaphor approach. The findings reveal that the cartoons showed different visual/ pictorial and multimodal metaphors in the sampled cartoons. They addressed different themes in satirical way. In conclusion, the verbal text played a role to make the multimodal metaphors dominant in the gathered cartoons that are relevant to social media.